2019
DOI: 10.1111/edt.12462
|View full text |Cite
|
Sign up to set email alerts
|

Through the ages—Aetiological changes in maxillofacial trauma

Abstract: Aims The number of patients suffering maxillofacial trauma remains constant although the affected patients become older. The aim of this study was to illuminate the patterns of maxillofacial fractures in a University Medical Centre and to analyse potential changes in patient population and treatment methods during a 5‐year period. Materials and methods In a retrospective analysis, the records of 573 patients with maxillofacial fractures treated in a level one trauma centre from January 2010 to December 2014 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 29 publications
5
24
1
9
Order By: Relevance
“…Fabio Roccia and Paolo Boffano carried out a study and found that among 132 patients, 15 patients had fall on the same level and 24 had fall from one level to another. In work‐related injuries, mandible fractures were most common (Goedecke & Thiem, 2019 ; Roccia et al, 2013 ) 26This is consistent with The current study as well. The second most common etiological factor of falls in the current study; occupational falls, resulted mostly in mandibular fractures.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Fabio Roccia and Paolo Boffano carried out a study and found that among 132 patients, 15 patients had fall on the same level and 24 had fall from one level to another. In work‐related injuries, mandible fractures were most common (Goedecke & Thiem, 2019 ; Roccia et al, 2013 ) 26This is consistent with The current study as well. The second most common etiological factor of falls in the current study; occupational falls, resulted mostly in mandibular fractures.…”
Section: Discussionsupporting
confidence: 91%
“…had fall from one level to another. In work-related injuries, mandible fractures were most common (Goedecke & Thiem, 2019;Roccia et al, 2013) • Environmental and occupational factors are most common etiologies of falls.…”
Section: T a B L E 1 Age Distribution Of The Samplementioning
confidence: 99%
“…Their causes and frequency vary from region to region [1][2][3][4], and result from the socio-economic status of patients, their education, and cultural and environmental factors, as well as alcohol consumption [5][6][7]. According to the World Health Organization, maxillofacial injuries are most frequently caused by road collisions, violence, or sports injuries [2,4,7]. These may result in injuries to the soft tissues of the face and mouth, the teeth, and fractures of the craniofacial bones [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The complex mаxillofаciаl trаumа with wide-spreаd soft-tissue defects hаs the potentiаl to cаuse disfigurement аnd loss of function; for exаmple, blindness or difficulty moving the jаw cаn result [1][2][3]. Furthermore, the complex mаxillofаciаl trаumа usuаlly connects closely to trаumаtic brаin injury, thorаcic trаumа аnd neаrby orgаns injury [2,4,5].…”
Section: Introductionmentioning
confidence: 99%